Trauma Rehabilitation After War and Conflict Community and Individual Perspectives - Martz, Erin.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
"As foreign assistance flows into post-conflict regions to rebuild economies, roads, and schools, it is important that development professionals retain a focus on the purely human element of rebuilding lives and societies. This book provides perspective on just how to begin that process so that the trauma people suffered is not passed on to future generations long after the violence has stopped." - Amy T. Wilson, Ph.D., Gallaudet University, Washington, DC "This ground-breaking text provides the reader with an excellent and comprehensive overview of the existing field of trauma rehabilitation. It also masterfully navigates the intricate relationships among theory, research, and practice leaving the reader with immense appreciation for its subject matter." -Hanoch Livneh, Hanoch Livneh, Ph.D., LPC, CRC, Portland State University Fear, terror, helplessness, rage: for soldier and civilian alike, the psychological costs of war are staggering. And for those traumatized by chronic armed conflict, healing, recovery, and closure can seem like impossible goals. Demonstrating wide-ranging knowledge of the vulnerabilities and resilience of war survivors, the collaborators on Trauma Rehabilitation after War and Conflict analyze successful rehabilitative processes and intervention programs in conflict-affected areas of the world. Its dual focus on individual and community healing builds on the concept of the protective "trauma membrane," a component crucial to coping and healing, to humanitarian efforts (though one which is often passed over in favor of rebuilding infrastructure), and to promoting and sustaining peace. The book$1 (Bs multiple perspectives$1 (Bincluding public health, community-based systems, and trauma-focused approaches$1 (Breflect the complex psychological, social, and emotional stresses faced by survivors, to provide authoritative information on salient topics such as: Psychological rehabilitation of U.S. veterans, non-Western ex-combatants, and civilians Forgiveness and social reconciliation after armed conflict Psychosocial adjustment in the post-war setting Helping individuals heal from war-related rape The psychological impact on prisoners of war Rehabilitating the child soldier Rehabilitation after War and Conflict lucidly sets out the terms for the next stage of humanitarian work, making it essential reading for researchers and professionals in psychology, social work, rehabilitation, counseling, and public health.s
to Trauma Rehabilitation After War and Conflict -- Exploring the Trauma Membrane Concept -- Forgiveness and Reconciliation in Social Reconstruction After Trauma -- A Public-Health View on the Prevention of War and Its Consequences -- Community-Based Rehabilitation in Post-conflict and Emergency Situations -- A Systems Approach to Post-conflict Rehabilitation -- Human Physical Rehabilitation -- Psychological Rehabilitation for US Veterans -- Psychological Rehabilitation of Ex-combatants in Non-Western, Post-conflict Settings -- Psychosocial Rehabilitation of Civilians in Conflict-Affected Settings -- Shame and Avoidance in Trauma -- Psychosocial Adjustment and Coping in the Post-conflict Setting -- Helping Individuals Heal from Rape Connected to Conflict and/or War -- The Psychological Impact of Child Soldiering -- The Toll of War Captivity: Vulnerability, Resilience, and Premature Aging -- Trauma-Focused Public Mental-Health Interventions: A Paradigm Shift in Humanitarian Assistance and Aid Work.
Keywords: Social sciences; Rehabilitation; Social work; Applied psychology; Social Sciences; Social Work; Psychotherapy and Counseling; Rehabilitation